A study to assess awareness about Janani Suraksha Yojana among beneficiaries of urban slums of Raipur city, Chhattisgarh - Khes, Shanta P.; Sahu, Divya; Soni, G. P.; Chandrakar, Aditi (International Journal Of Community Medicine And Public Health, 2017)
Background: Janani Suraksha Yojana (JSY) under the overall umbrella of National Rural Health Mission has been launched from April 2005. The scheme replaces the National Maternity Benefit Scheme. It aims at increasing institutional delivery, thereby reducing maternal and neonatal mortality. The objectives of the study were to assess awareness regarding JSY and to assess role of factors contributing in awareness. Methods: A community based Cross-sectional observational study was conducted in urban slum of Raipur city among 384 mothers delivered within last one year. Study centre was Department of community medicine, Pt J.N.M. medical college Raipur, Chhattisgarh. The subjects were interviewed using a pre-designed and pre-tested questionnaire. Results: Majority of the study subjects were not aware about the services under JSY except for the monetary benefit. Though a very small proportion of beneficiaries know the name of the scheme, majority delivered in the health facility. Conclusions: To increase awareness regarding other components under JSY and to achieve 100% institutional delivery there is need to strengthen effective IEC along with active involvement of ASHA.